2007
DOI: 10.1038/sj.pcan.4500979
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, vegetable, vitamin A intakes, and prostate cancer risk

Abstract: Prostate cancer risk was examined in relation to intakes of fruit, vegetables, b-carotene and retinol. Subjects were a cohort of 1985 men previously to asbestos who participated in a cancer prevention programme of b-carotene and retinol supplements that commenced in July 1990. Diet was assessed at entry to the programme. Ninety-seven cases of prostate cancer were identified during follow-up until the end of 2004. A decreased prostate cancer risk was observed with increasing intakes of vitamin C-rich vegetables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 27 publications
2
37
0
1
Order By: Relevance
“…Some studies reported a reduction in prostate cancer risk associated to increasing intakes of vitamin C [11,18] or vitamin C-rich vegetables [19], while other studies showed no association between vitamin C and prostate cancer [4,9,20,21].…”
mentioning
confidence: 99%
“…Some studies reported a reduction in prostate cancer risk associated to increasing intakes of vitamin C [11,18] or vitamin C-rich vegetables [19], while other studies showed no association between vitamin C and prostate cancer [4,9,20,21].…”
mentioning
confidence: 99%
“…12 vitamin C has role in regeneration of tocopherol from phenoxy free radical derivative 13 vitamin E and Vitamin C levels are reduced in prostate cancer patients. 14 Insulin can mediate its mitogenic effect on prostate cells through signal transduction mechanism. Recent physiological and genetic studies have levels that the insulin signaling pathway plays a pivotal role in the regulation of variety of interrelated fundamental processes such as metabolism, growth, reproduction, and aging the mammalian target of rapamyanis a downstream molecule of the P13K / PTEN -AKT-mTOR pathway of insulin and IGF -1 receptor this signaling network lays a crucial role in the translational level by modifying phosphorylation of pivotal targets such as the translation initiation factor GE-binding proteins and S6KS.…”
mentioning
confidence: 99%
“…Indeed, lower levels of inflammation and increases in antioxidants have been correlated to fruit and vegetable intake (Root et al, 2012). While not all studies concur (Ambrosini et al, 2007;Boffetta et al, 2010), there is evidence suggesting benefit from vegetable and fruit intake in regards to prostate cancer (Riso et al, 1999;Hardin, Cheng & Witte, 2011;Shahar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%